Mistletoe species richness patterns are influenced more by host geographic range than nitrogen content. (13th July 2016) - Griffiths, Megan E.; Ruiz, Natalia; Ward, David
Abstract: Mistletoes are hemiparasites that access water and nutrients from their hosts. Previous studies have suggested that host genera with high nitrogen are parasitized by more mistletoe species but these studies failed to take into account phylogenetic relationships among host genera. Our main question was whether more mistletoe species parasitize host genera with high nitrogen content when phylogenetic relationships were controlled. We also asked whether patterns in mistletoe parasitism were related to host geographic range size, host fruit type and host spinescence. Overall, we found no difference between conventional and phylogenetically controlled analyses. We also found no evidence for higher mistletoe species richness on host genera with high nitrogen, fleshy fruits or spinescence. However, similar to findings for animal parasites, we found that host genera with large geographic range had higher mistletoe species richness. This is likely because a greater number of mistletoe species will encounter hosts that have a greater geographic distribution. Mistletoe studies frequently assume that nitrogen status drives patterns in mistletoe parasitism but our study suggests that macroecological patterns in mistletoe assemblages are primarily determined by host geographic range.